Implementation of STEAM-based digital learning for students' numeracy literacy in elementary schools - Rahma Hidayanthi; Nurul Husna Siregar; Dedes Asriani Siregar; Hotmaida Lestari Siregar (Research and Development in Education (RaDEn), 2024)
The lack of optimal empowerment of effective numeracy literacy at the elementary school level can result in less-than-optimal mathematics learning outcomes for students. This research aims to see the effect of implementing digital learning integrated with the STEAM approach on the numeracy literacy of fifth grade elementary school students. This research combines experimental and quantitative methods with Nonequivalent Control Group Design. The sample was 40 students from classes VA and VB at SDN 200304 Padangsidimpuan City who were selected using purposive sampling. The research results show an increase in students' numeracy literacy skills after using STEAM-based learning media. In conclusion, the application of digital learning with the STEAM approach has a positive impact on increasing the numeracy literacy of elementary school students.